2006
DOI: 10.1002/erv.739
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between self‐discrepancies, eating disorder and depressive symptoms in women

Abstract: At least one generic self-discrepancy is related specifically to eating disorder rather than depressive symptoms. Implications of the findings for theory and clinical practice are briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…This is not surprising, as anorexic patients have been described, since the first clinical reports in this field, as individuals who try to achieve perfection in every area of their lives (Bruch 1978). In a similar vein, Sawdon et al (2007) found that the discrepancy between actual self and potential self distinguished eating disordered patients from those who were primarily depressed. It could, therefore, be stated that self-perceptions contributing to depression are based on who you are, whereas self-perceptions associated with eating disorders are focused on who you may become.…”
Section: Discussionmentioning
confidence: 82%
“…This is not surprising, as anorexic patients have been described, since the first clinical reports in this field, as individuals who try to achieve perfection in every area of their lives (Bruch 1978). In a similar vein, Sawdon et al (2007) found that the discrepancy between actual self and potential self distinguished eating disordered patients from those who were primarily depressed. It could, therefore, be stated that self-perceptions contributing to depression are based on who you are, whereas self-perceptions associated with eating disorders are focused on who you may become.…”
Section: Discussionmentioning
confidence: 82%
“…This longitudinal study provided novel evidence for the association between cognitive factors, taking into account automatic thoughts about eating [ 1 ], weight discrepancies [ 10 13 ], and ED symptoms within a non-clinical sample of adolescents. In line with the cognitive ED models [ 1 , 6 ] and in line with the self-discrepancy theory [ 10 ], it was assumed that these factors would play an important role in the process of formation and maintenance of ED symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, individuals tend to reduce arising discrepancies. Self-discrepancy theory can be adopted to explaining effects of body weight and shape evaluations on ED symptoms formation [ 10 13 ]. As far as ED are concerned, the most striking discrepancies may occur between the actual-self and ideal-self (in bulimia), and the actual-self and ought-self (in anorexia) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Wonderlich et al () found that both A:I and A:O discrepancies were elevated in those with BN versus controls. However, Sawdon, Cooper, and Seabrook () found no significant correlations between ED symptoms (measured using the Eating Attitudes Test) and A:I or A:O among a community sample of 100 women.…”
mentioning
confidence: 99%